RF CMOS Wireless Implantable Microsystem for Sacral Roots Stimulation with On-Chip Antenna and Far-Field Wireless Powering - Rodrigues, Filipe Joel Costa (2015)
The use of heterogeneous integration technologies is the path for the development of further miniaturized, smarter, and energy autonomous microdevices, which are required to tackle the challenge of monitoring and/or control the health condition of everyone, everywhere. The interaction with human body requires the use of flexible materials, while the electronic component are based on rigid materials, like silicon substrates. Also, once inside the human body, it is desirable to have a wireless link for data communication, as well for RF powering, using energy harvesting techniques or dedicated powering RF links. This paper shows the design of an implantable microsystem to be used for functional electrical stimulation of sacral roots. The proposed system includes flexible electrodes, integrated with an RF CMOS chip, which is powered by a wireless link through an efficient on-chip antenna.